A Cross-Sectional Study on Impact and Relationship between Screen Time and Academic Productivity among Medical Students in University of Ilorin - Ojo-Rowland, O. T.; Oyewopo, T. G.; Ekunnrin, O. A.; Salawu, O. V.; Adetokunbo, H. K.; Malomo, V. A.; Osborn, G. K.; Owolabi, O. O.; Yusuf, T. O.; Ibrahim, H.; et al. (British Journal of Healthcare and Medical Research, 2026)
The increasing integration of digital technologies into higher education has led to a substantial rise in digital screen time among university students, particularly those in demanding academic programs such as medicine. This study assessed the pattern and association between digital screen time and academic productivity among medical students at the University of Ilorin, Nigeria. An institutional based descriptive cross-sectional design was employed, involving 360 medical students selected through multistage sampling. Data were collected using a semi-structured, self-administered questionnaire assessing demographic characteristics, screen time exposure, purposes of screen use, academic productivity, and perceived academic impact. Descriptive and inferential analyses were conducted using SPSS version 25, with statistical significance set at p < 0.05. The findings revealed a high prevalence of excessive screen time (73.1%), with over two-thirds of respondents (58.1%) engaging in prolonged daily screen exposure, predominantly during nighttime and before bedtime. Smartphones were the most commonly used devices, mainly for academic activities, social media, and communication. Most respondents demonstrated moderate academic productivity, while a smaller proportion showed high productivity. A significant association was identified between screen time exposure and academic productivity, and regression analysis indicated that average daily screen time was a significant predictor of productivity, although the overall explanatory power of the model was minimal These findings suggest that while excessive screen time is widespread among medical students, its impact on academic productivity is complex and influenced by the purpose and pattern of use. The study highlights the need for targeted interventions that promote balanced and purposeful digital engagement to optimize academic outcomes among medical students.